Analysis by ICP-MS spectrometry and ICP-OES spectrometry techniques for elements contained in residual powder of fluorescent lamps (International Seven Journal of Multidisciplinary, 2023)
The process of lighting public and private areas was an important point for the well-being of humanity and guaranteeing public and residential safety. The advances in luminous devices achieved by distinguished scientists such as Thomas Edson, Nicola Tesla, among others, were fundamental for the advancement of humanity's progress. However, the harmful effect on the environment generated by the residue of these new lighting devices must be taken into account. Environmental engineering, above all, plays an important role by analyzing and evaluating the degree of these residues and guaranteeing a sustainable industrial process, especially in this 21st century where it is increasingly necessary to measure possible environmental impacts. Fluorescent lamps are one of the lighting devices that must be constantly studied. The present research was focused on evaluating, through the subsidy of ICP spectrometry techniques, the chemical compounds present in waste fluorescent lamps, in order to have a vision of the elements contained and their impact on the leaching process. Such research carried out with the support of the UNICAMP chemical center was vital for the implementation of this study as an initial starting point for future discussions on other future projects. The values obtained from the chemical elements were tabulated and showed the reflection of these residues presents.